2005
DOI: 10.1074/jbc.m504369200
|View full text |Cite
|
Sign up to set email alerts
|

RIC-3 Affects Properties and Quantity of Nicotinic Acetylcholine Receptors via a Mechanism That Does Not Require the Coiled-coil Domains

Abstract: Members of the RIC-3 gene family are effectors of nicotinic acetylcholine receptor (nAChR) expression in vertebrates and invertebrates. In Caenorhabditis elegans RIC-3 is needed for functional expression of multiple nAChRs, including the DEG-3/DES-2 nAChR. Effects of RIC-3 on DEG-3/DES-2 functional expression are found in vivo and following heterologous expression in Xenopus leavis oocytes. We now show that in X. leavis oocytes RIC-3 also affects the kinetics and agonist affinity properties of the DEG-3/DES-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 14 publications
(28 reference statements)
9
80
0
Order By: Relevance
“…Although the coiled-coil domain is highly conserved in all known RIC-3 family members, previous studies on other mammalian receptors have found that its deletion has no effect on the ability of RIC-3 to enhance (or depress) expression (Ben-Ami et al, 2005;Castillo et al, 2005;Cheng et al, 2007;Lansdell et al, 2008). Recent studies have shown that in C. elegans, a RIC-3 coiled-coil domain homologous to that in mRIC-3 is required for full expression of some, but not all, nAChRs (Biala et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the coiled-coil domain is highly conserved in all known RIC-3 family members, previous studies on other mammalian receptors have found that its deletion has no effect on the ability of RIC-3 to enhance (or depress) expression (Ben-Ami et al, 2005;Castillo et al, 2005;Cheng et al, 2007;Lansdell et al, 2008). Recent studies have shown that in C. elegans, a RIC-3 coiled-coil domain homologous to that in mRIC-3 is required for full expression of some, but not all, nAChRs (Biala et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanisms by which the hRIC-3 protein exerts its effects on nicotinic receptors are not known. It has been reported that the N-terminal and the C-terminal regions of hRIC-3 are involved in its action on α7 nAChRs (Ben-Ami et al, 2005) and 5HT3Rs (Cheng et al, 2007;Cheng et al, 2005). Because of the close sequence similarity between nAChRα7 and nAChR α9 subunits (42% identity at the amino acid level), we utilized in vitro and in vivo co-immunoprecipitation analyses and confirmed that α9 and hRIC-3 are able to co-associate directly in HEK293T cells and cochlear tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For RIC-3 mRNA expression, primers based on mouse RIC-3 sequence amplify a unique PCR fragment contained within the transmembrane region that is essential for mediating interactions with nAChR subunits (Ben-Ami et al, 2005). In Figure 1d, RIC-3 is expressed at relatively low levels at E18, higher levels between P0 and P10, and significantly reduced levels beginning at P18 levels.…”
Section: Endogenous Expression Of Nachr Accessory Proteins During Devmentioning
confidence: 99%
“…Moreover, RIC-3 was shown to affect properties (kinetics of desensitization and affinity to acetylcholine) of the C. elegans DEG-3/DES-2 nAChR. These effects were attributed to a RIC-3-dependent increase in the DEG-3 to DES-2 stoichiometry of this receptor, likely to be the result of preferential interaction between RIC-3 and the DEG-3 subunit, leading to its preferential insertion into the mature receptor 24,25 .…”
Section: Maturation Of Nachrs and The Ric-3 Proteinmentioning
confidence: 99%
“…Additionally, brain expression patterns of mouse ric3 mRNA and CHRNA7 overlap, a result consistent with the suggestion that mammalian RIC-3 is required for α7 nAChR's maturation in vivo 19 . RIC-3 was shown to affect stability of unassembled nAChR subunits, assembly of subunits to form a nAChR, and trafficking of nAChRs [24][25][26][27][28][29] ( Figure 1 and below). In C. elegans loss of ric-3 gene function led to reduced plasma membrane expression of multiple nAChRs, demonstrating a positive, nAChR expression promoting function for RIC-3 22 .…”
Section: Maturation Of Nachrs and The Ric-3 Proteinmentioning
confidence: 99%